India’s Story of Reducing Maternal Mortality - Achievement so far and Commitments Ahead - Kansal, Amrita; Kandpal, S D (Indian Journal of Community Health, 2018)
In the year 2000, the United Nations (UN) Member States pledged to work towards a series of Millennium Development Goals (MDGs), including the target of a three-quarters reduction in the 1990 Maternal Mortality Ratio (MMR; maternal deaths per 100 000 live births), to be achieved by 2015. This target (MDG 5A) and that of achieving universal access to reproductive health (MDG 5B) together formed the two targets for MDG 5: Improve maternal health (1).